2019
DOI: 10.1002/iub.2001
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIAT facilitates osteosarcoma progression by regulating mir‐128‐3p/VEGFC axis

Abstract: The aberrant expression of long non‐coding RNAs (lncRNAs) has been involved in the progression of many human tumors including osteosarcoma (OS). However, the biological function and the underlying mechanism of the lncRNA myocardial infarction‐associated transcript (MIAT) in OS remain unclear. In the present study, we found that lncRNA MIAT was significantly up‐regulated in both OS tissues and cell lines, and high expression of MIAT was positively associated with tumor size and lymph node metastasis of OS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Thus, investigating the crosstalk between lncRNAs and miRNAs will be helpful for improving our understanding of lncRNAs. To date, several miRNAs have been reported to be sponged by MIAT, including miR-149-5p [30], miR-150-5p [31], miR-128-3p [32], and miR-29c [33]. Of note, miR-132, a key miRNA involved in chondrogenic differentiation [17], was also found to be sponged by MIAT in colorectal cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigating the crosstalk between lncRNAs and miRNAs will be helpful for improving our understanding of lncRNAs. To date, several miRNAs have been reported to be sponged by MIAT, including miR-149-5p [30], miR-150-5p [31], miR-128-3p [32], and miR-29c [33]. Of note, miR-132, a key miRNA involved in chondrogenic differentiation [17], was also found to be sponged by MIAT in colorectal cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…These results were further supported by the colony formation assays, which indicated that miat knockdown significantly inhibited the HCC cells colony formation (Figure 2G, 2H and Supplementary Figure 1Q, 1R). It has been reported that miat was associated with metastasis of solid tumors [30]. Therefore, we conducted the migration ability of miat by Transwell and Wound-healing assays.…”
Section: Resultsmentioning
confidence: 99%
“…So, the precious results and our present study demonstrated lnc-SNHG16 could be target for prevention and therapeutics for CC in future. miR-128 was low expression in osteosarcoma [24], glioma [25], ovarian cancer [26], thyroid cancer [27], HCC [28], CRC [29], gastric carcinoma (GC) [30]. However, the role and mechanism of miR-128 remains unclear in CC.…”
Section: Discussionmentioning
confidence: 99%